A Comparative Study of Over-the-Counter Drug Regulations in India and United States of America and European Union - Raju, K. Venkateswara (Asian Journal of Pharmaceutics (AJP), 2023)
To convert an Rx to an over-the-counter (OTC) version, the drug must have some intrinsic characteristics that make it suitable for self-medication. Although definitions vary by country, the prescription to OTC-switch refers to the conversion of established Rx to OTC classification and done in scenario where the drug must have an extremely high safety limit, it is used in clearly defined circumstances, simple to use, the drug’s use potentially hazardous conditions are not be concealed. The pandemic of COVID-19 had a vital effect on the market. India’s manufacturers depend largely on Chinese imports of active pharmaceutical ingredients (APIs). The lockdown slowed API output, resulting in less accessibility and more material prices for the products. Due to the huge demand for necessary OTC medications, the government limited the export of some essential medicines. Aside from OTC pain relievers and fever reducer paracetamol, medicines restricted for export include metronidazole and other components containing Vitamin B1 and B12 as well as antibiotics used to treat bacterial and other diseases. On the other side, online purchases of OTC medications have increased. His study focused on a comparative study of OTC drug regulations in India and United States of America and the European Union